Cycling Kinematics Analysis using Image Processing - Teo, Chou Wen (Universiti Malaysia Sarawak, (UNIMAS), 2019)
Cycling kinematics are important for cyclists since it helps them to improve their performance and decreased the chance to get injured. Besides, it helps the physiotherapists and sports personnel to perform an onsite quick check. This research is about the analysis of cycling kinematics by using image processing. The data for this project is videos of cyclist cycling with three red markers on the hip, knee, and ankle’s joint position. The proposed algorithm successfully detected the manually added red markers for the calculation of the angle of the joints.